A comparative measure of inclusive urbanisation in the cities of Africa. (June 2021) - Angelopulo, George
Abstract: Africa has the swiftest rate of urbanisation in the world and with it varying possibilities of improved quality of life or the entrenchment of poverty and inequality in the cities of the continent. In this paper an instrument that measures and compares African urban development from the perspective of inclusive urbanisation is specified, tested and refined. The theoretical model for the instrument is generated from the literature on inclusive urbanisation and developed to assess the potential inclusivity of cities as much as their current state. The instrument is applied to a cluster of cities across the continent and a small number of comparison cities in Asia and Latin America with baseline data from the 2014 period to form a ranking of cities by their potential for inclusive urbanisation. The city ranking that it yields is then assessed in numerous correlation tests with data on achieved performance in key areas of inclusive urbanisation from a period five years later, and the instrument revised in three areas for efficacy and parsimony. The first revision lies in its constitution of variables, the second in the model of the instrument, and the third in its statistical construction. The study finds that the revised instrument, the Inclusive Urbanisation Index, yields better results in predicting inclusive urbanisation than the original instrument. It shows that the dominant factors determining inclusive urbanisation may be limited to a narrow range of infrastructure, human development, economic and governance indicators rather than the broad range originally identified in the literature. Most significantly the study also finds that rapid population growth over the 2014–19 period – a key driver of urbanisation in Africa – correlates very poorly with the expansion of inclusive conditions among African cities as a class, acting more as a burden than the positive dividend that had been widely anticipated to flow from that growth.